Short Communication: Variation in isozymic pattern of germplasm from three ginger (Zingiber officinale) varieties - AHMAD DWI SETYAWAN; WIRYANTO WIRYANTO; SURANTO SURANTO; NURLIANI BERMAWIE (Nusantara Bioscience, 2014)
Abstract. Setyawan AD, Wiryanto, Suranto, Bermawie N. 2014. Variation in isozymic pattern of germplasm from three of ginger (Zingiber officinale) varieties. Nusantara Bioscience 6: 86-93. Ginger (Zingiber officinale Rosc.) has long been as spices, flavoring agent and raw material for herbal medicines. In Indonesia, there were three varieties based on color and size of the rhizome, i.e. gajah (big-white ginger), merah (red ginger), and emprit (small-white ginger). This research was conducted to find out: (i) isozymic pattern of three ginger varieties, and (ii) phylogenetic relationship of those three varieties. The plant materials were gathered from Wonogiri, Surakarta and Kulonprogo, Yogyakarta. Two enzyme systems, namely esterase (EST) and peroxidase (PER, PRX) were used in this study. The relationship among ginger varieties was determined by UPGMA. The result indicated that EST showed two bands (i.e. Rf 0.04 and 0.10), and PRX showed six bands (i.e. Rf 0.04, 0.05, 0.09, 0.10, 0.11, and 0.15). Peroxidase produces more numerous and more diverse isozymic bands than esterase, resulting in a more complex relationship. The data used to compile dendrogram affect the grouping; the more data used, the more obvious clustering of accessions in a population. Dendrogam generated from esterase and peroxidase banding patterns produced distinct clusters based on varieties and location.